Carrier confinement effects observed in the normal-state electrical transport of electron-doped cuprate trilayers. (1st February 2019) - Sacco, Chiara; Galdi, Alice; Romeo, Francesco; Coppola, Nunzia; Orgiani, Pasquale; Wei, Haofei I; Goodge, Berit H; Kourkoutis, Lena F; Shen, Kyle; Schlom, Darrell G; Maritato, Luigi
Abstract: SrCuO2 /Sr0.9 La0.1 CuO2 /SrCuO2 trilayers were grown by oxide-molecular beam epitaxy. The thicknesses of the top and bottom SrCuO2 layers were fixed, while the thickness of the infinite-layer electron-doped cuprate Sr0.9 La0.1 CuO2 central layer was systematically changed. Transmission electron microscopy, x-ray reflectivity and x-ray diffraction measurements were performed to assess the sample quality and the abruptness of the interfaces. Electrical transport measurements as a function of temperature and as a function of central layer thickness, confirm that the normal state properties of the trilayers are altered by the confinement of the charge carriers in the central layer.